Social context and consequences of mental illness in changing scenario - Anand Kumar; Prashant Srivastava; Pradeep Kumar; Manisha Kiran (Open Journal of Psychiatry and Allied Sciences, 2015)
Mental illness has very close and intimate relationship with societal factors and components. There have been many theoretical postulations that come from time to time to explain this relationship. Mental disorder has definite aetiological association with various socio-cultural and economic factors, and ideal interventions of mental disorders should include equal appraisal to biological, psychological, and social aspects.